1998
DOI: 10.1111/j.1748-0361.1998.tb00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Quality of Life of Rural Families

Abstract: Drawing from human ecology theory, the purpose of this study was to examine socioeconomic-demographic determinants of the quality of life of rural families. In the study, computer-aided telephone interviewing via random digit dialing procedures were used to collect data in the spring of 1996. The participants included 510 rural (both farm and nonfarm) respondents. Quality of life was measured by five subscales: finances; home, family, and friends; household; community; and environment. The results of the regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In line with the findings of Garrison's (1998) study ( 35 ), we observed lower levels of life satisfaction among respondents with one or more chronic medical conditions. According to previous studies, poor health is detrimental to mental health and happiness, affecting an individual's daily life and reducing their life satisfaction ( 4 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with the findings of Garrison's (1998) study ( 35 ), we observed lower levels of life satisfaction among respondents with one or more chronic medical conditions. According to previous studies, poor health is detrimental to mental health and happiness, affecting an individual's daily life and reducing their life satisfaction ( 4 ).…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence that perceptions of health and use of the health system are different for people in rural communities (31,42,53,103), and this may influence the course of treatment and how issues of health and illness are viewed by rural clinicians and patients (72,81,99,100). For example, rural people may more often tend to delay treatment.…”
Section: Rural Health Professionalsmentioning
confidence: 99%
“…The composition of the household may also have an effect on place attachment (Garrison 1998). Having children is an important intermediary in generating social contacts, which, in turn, results in higher social attachment (Parkes, Kearns, and Atkinson 2002).…”
Section: Facilities and Other Factors Affecting One's Social Place Atmentioning
confidence: 99%